2003
DOI: 10.17221/4706-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fertilisation on Norway spruce needles

Abstract: ABSTRACT:Yellowing of Norway spruce is a relatively common problem in many regions of the Czech Republic. At some places, it is also connected with forest decline. This unfavourable phenomenon is initiated by several ecological as well as anthropogenic processes. One of the most important is the imbalance of forest stand nutrition. Particular reasons lead to nutrient deficiency, especially deficiency of magnesium. Solution to this undesirable trend is a profound ecological analysis and cause-oriented treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Many specialists studied fertilization and liming as possible revitalization treatments in declining Norway spruce forest stands (Badalík, Řezáč 2001;Musil, Pavlíček 2002;Podrázský et al 2003;Schaaf, Hüttl 2006) or as measures to increase the volume increment (Derome et al 1986;Materna 2001). On the other hand, the complex analyses of aerial spraying and quality (variability) of aerial application of both fertilizer (using a crop duster) and dolomitic limestone (using a helicopter) have not been performed yet.…”
Section: Resultsmentioning
confidence: 99%
“…Many specialists studied fertilization and liming as possible revitalization treatments in declining Norway spruce forest stands (Badalík, Řezáč 2001;Musil, Pavlíček 2002;Podrázský et al 2003;Schaaf, Hüttl 2006) or as measures to increase the volume increment (Derome et al 1986;Materna 2001). On the other hand, the complex analyses of aerial spraying and quality (variability) of aerial application of both fertilizer (using a crop duster) and dolomitic limestone (using a helicopter) have not been performed yet.…”
Section: Resultsmentioning
confidence: 99%
“…In their studies, Vacek et al (2006) and Podrázský et al (2003b) report that optimization of Norway spruce nutrition as well as reduced defoliation and discoloration occurred after the application. The research area of Suchdol showed in the first growing season slight positive effect of calcareous dolomite on the foliar calcium and magnesium concentrations.…”
Section: Discussion the Effect Of Fertilizers On The Concentration Ofmentioning
confidence: 99%
“…indicated decreasing availability not only of P but also of Mg, which in combination with soil acidification may be limiting factors for the forest nutrition in the future (Lomský et al 2012). On poor sites under former acidification stress the improved nutrient supply may act as a stimulus promoting growth and influencing the vitality and survival of especially young trees (Nilsen, Abrahamsen 2003;Podrázský et al 2003;Kupka 2005;Óskarsson et al 2006). Liming increasing the Ca and Mg supply can partly improve the accessibility of P (Formánek, Vránová 2002).…”
Section: Discussionmentioning
confidence: 99%